A Critique on the Book The Topkapi Scroll-Geometry and Ornament in Islamic Architecture - Maryam Kamyar (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
A Study of Geometry in Islamic Architecture by Professor Golroo Najibaaghlou is a valuable work in the field of Islamic architecture. This book has a detailed preface, a brief introduction, and five main sections. As it is known from the introduction of the book, this book was originally written for a non-Iranian audience. The first purpose of writing this book is to try to moderate public belief about geometry and the stages of compilation and discussion in Islamic architecture. Another purpose is to correct the negative view of the geometric documentation of Islamic architecture in the West, because such a view has created a kind of reluctance to equate the works of Islamic architecture with the great works of classical Western architecture. In addition, Najibaaghlou wants to reject and respond to Western criticism that reduces Islamic architecture to the level of an unedited work. In the final chapter of the book, Najibaaghlou looks at the compiled documents of Islamic architecture from a Western perspective and highlights some of the missed points of geometric sciences, including clarifying conceptualization, recording, and transferring architectural design in the Islamic world.